ANALISIS KEUNTUNGAN INDUSTRI PENYULINGAN MINYAK DAUN CENGKEH DI DESA ATOGA KECAMATAN MOTONGKAD KABUPATEN BOLAANG MONGONDOW TIMUR (Profit Analysis of Clove Leaf Oil RefiningIndustry in Atoga Village, Motongkad Distric, East Bolaang Mongondow Regency) - Nahdayana Dewi Ginoga; Theodora M. Katiandagho; Audrey J. M. Maweikere (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The purpose of this study was to analyze the profits and to determine the Break Event Point (BEP) of the Home Industry of Clove Leaf Oil Refining in Atoga Village, Mongkad District, Bolaang Mongondow Timur Regency. This research was carried out from December 2021 to March 2021. The sampling method in this study was the Purposive Sampling method. The data used in this study were primary data obtained through direct interviews with farmers using a list of questions (questionnaires) that have been prepared and field observations, and secondary data obtained from the internet and related agencies. Data Analysis used in this study was the analysis of business profits in one week or two times ofÂ the production process and calculating the Break Event Point (BEP) of clove leaf oil refining as well asÂ analyzing the business feasibility of R/C.